The Origin of The Emergence of Arabic Lexicology And Its Characters / Cikal Bakal Munculnya Leksikologi Arab dan Para Tokoh-Tokohnya - Balkis Aminallah Nurul Mivtakh (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This article aims to examine the history of Arabic lexicology in the classical era and the figures who contributed to the field of Arabic lexicology. There are three questions that will be answered through this research, namely First, "How was the forerunner to the development of Arabic lexicology in the classical era?". Second, "Who played an important role in spreading and introducing Arabic lexicology?". Third, "what works have been produced by Arab lexicological scientists in the early days of their development?". This study uses a qualitative research method based on literature study related to Arabic lexicological literature. The results of this study are: First, the history of Arabic lexicology in the classical era began with the lahn event (language error), then the event gave rise to the idea of ​​scholars to record Arabic vocabulary through the Bedouin tribe, while the methods used in language codification were the sima' and qiyas methods. . Second, figures who are instrumental in Arabic lexicology include Khalil bin Ahmad Al-Farahidi, Abu Mansur Al-Azhari, Ibn Jinni, and Ibn Fariz. Third, the works produced by lexicological scientists from the classical era, namely: the al-ain dictionary by Khalil bin Ahmad Al-Farahidi, the tahdzib al-lughah dictionary by Abu Mansur al-Azhari, the book of al-khosois by Ibn Jinni, and maqoyis lughoh by Ibn Faris.